COVID-19 in Lung Transplant Recipients. Issue 1 (January 2021) - Messika, Jonathan; Eloy, Philippine; Roux, Antoine; Hirschi, Sandrine; Nieves, Ana; Le Pavec, Jérôme; Sénéchal, Agathe; Saint Raymond, Christel; Carlier, Nicolas; Demant, Xavier; Le Borgne, Aurélie; Tissot, Adrien; et al.
Abstract : Background: A concern about the susceptibility of immunocompromised patients to the worldwide pandemic of coronavirus disease 2019 (COVID-19) has been raised. We aimed at describing COVID-19 infections in the French cohort of lung transplant (LT) patients. Methods: Multicenter nationwide cohort study of all LT recipients with COVID-19 diagnosed from March 1 to May 19, 2020. Recipient main characteristics and their management were retrieved. Hospitalization characteristics, occurrence of complications and survival were analyzed. Results: Thirty-five LT patients with a COVID-19 infection were included. Median age was 50.4 (40.6–62.9) years, 16 (45.7%) were female, and 80% were double-LT recipients. Infection was community-acquired in 25 (71.4%). Thirty-one (88.6%) required hospitalization, including 13 (41.9%) in the intensive care unit. The main symptoms of COVID-19 were fever, cough, and diarrhea, present in 71.4%, 54.3%, and 31.4% of cases, respectively. Extension of pneumonia on chest CT was moderate to severe in 51.4% of cases. Among the 13 critically ill patients, 7 (53.9%) received invasive mechanical ventilation. Thrombotic events occurred in 4 patients. Overall survival rate was 85.7% after a median follow-up of 50 days (41.0–56.5). Four of 5 nonsurvivors had had bronchial complications or intensification of immunosuppression in the previous weeks. On univariate analysis, overweight was significantly associated with risk of death (odds ratio, 16.0; 95% confidence interval, 1.5-170.6; P  = 0.02). Conclusions: For the 35 LT recipients with COVID-19, the presentation was severe, requiring hospitalization in most cases, with a survival rate of 85.7%. Abstract : Supplemental Digital Content is available in the text.